Fabrication, characterisation and properties of polyvinyl alcohol/graphene nanocomposite for fused filament fabrication processing. (3rd July 2021) - Pei, Haoran; Yang, Lu; Xiong, Yu; Chen, Yinghong; Shi, Shaohong; Jing, Jingjing
ABSTRACT: In this study, graphene nanoplatelet (GNP) fillers were first mixed with a polyvinyl alcohol (PVA) aqueous solution under ultrasonication, and then glycerol was added as a plasticiser to enhance the thermal processability of the PVA/GNP mixture. The interactions among glycerol, GNP and PVA, rheological behaviour, crystallisation behaviour, electrical properties, and mechanical properties of the 3D printed parts were carefully investigated. The results show that the incorporation of glycerol can effectively decrease the melting temperature of PVA, thus improving the thermal FFF processability of the PVA/GNP nanocomposite. Besides, compared with the glycerol modified PVA (mPVA), the electrical conductivity of the mPVA/GNP nanocomposite 3D printed part with only 1.0 wt-% GNP loading could increase by ∼300 times (from 7.8 × 10 −7  S m −1 to 2.4 × 10 −4  S m −1 ). The obtained functional mPVA/GNP nanocomposite filaments were successfully used in fabrication of various 3D printed functional parts with complex geometry/structure and good dimensional accuracy.